Integrasi Pendekatan Pembelajaran Mendalam Ala Biggs & Tang dalam Kurikulum PIAUD untuk Penguatan Literasi Spiritual dan Kognitif Anak - Azhari, Muhammad (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2025)
This article explores the integration of the deep learning approach (as conceptualized by Biggs & Tang) into the Early Childhood Islamic Education (PIAUD) curriculum as an innovative strategy to holistically enhance children’s spiritual and cognitive literacy. Employing a descriptive qualitative method, the study analyzes relevant literature, current curriculum documents, and implementation in several Islamic-based PIAUD institutions. Findings indicate that this approach fosters contextual understanding of Islamic values, nurtures early critical thinking, and integrates spiritual, cognitive, and affective dimensions in learning. The novelty of this study lies in its emphasis on combining reflective pedagogy with tawhid-based Islamic values in early childhood curriculum design. It recommends a transformative, adaptive curriculum framework responsive to 21st-century educational challenges and the demands of the Fifth Industrial Revolution